Novel SUFU Frameshift Variant Leading to Meningioma in Three Generations in a Family with Gorlin Syndrome. (28th July 2019) - Askaner, Gustav; Lei, Ulrikke; Bertelsen, Birgitte; Venzo, Alessandro; Wadt, Karin
Abstract : Gorlin syndrome is mainly caused by pathogenic germline variants in the tumour suppressor genes PTCH1 and SUFU, both regulatory genes in the hedgehog pathway. However, the phenotypes of patients with PTCH1 and SUFU pathogenic variants seem to differ. We present a family with a frameshift variant in the SUFU gene c.954del, p.Asn319Thrfs∗ 42 leading to meningiomas and multiple basal cell-carcinomas.